Русские названия желудка (принципы номинaции) - Ушинскенe, В. (Kalbotyra, 1990)
A group of anatomical terms denoting stomach in Russian and in some of its dialects is being analysed in the paper. The terms that came into being at the time of dialectal differentiation of Proto-Slavonic and formation of independent Slavonic languages are in some cases semantically derived from words referring to the abdominal cavity, especially to that of animals. The established semantic patterns of derivation of such terms have practically remained unchanged up to the present time.